2017
DOI: 10.1308/rcsann.2017.0054
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the splenic flexure

Abstract: INTRODUCTION Anecdotally, surgeons claim splenic flexure mobilisation is more difficult in male patients. There have been no scientific studies to confirm or disprove this hypothesis. The implications in colorectal surgery could be profound. The aim of this study was to assess quantitatively whether there is an anatomical difference in the position of the splenic flexure between men and women using computed tomography (CT). METHODS Portal venous phase CT performed for preoperative assessment of colorectal mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…Besides, it has been long believed that male gender is a risk factor for di cult SFM. In a study on patients preoperative CT ndings, it has been concluded that the splenic exure is higher and further from midline in men than in women, and this nding provides the hypothesis why SFM is more di cult in male patients (20). However, the current study does not support this hypothesis, and have not revealed any signi cant association between gender and SFM duration.…”
Section: Discussioncontrasting
confidence: 82%
“…Besides, it has been long believed that male gender is a risk factor for di cult SFM. In a study on patients preoperative CT ndings, it has been concluded that the splenic exure is higher and further from midline in men than in women, and this nding provides the hypothesis why SFM is more di cult in male patients (20). However, the current study does not support this hypothesis, and have not revealed any signi cant association between gender and SFM duration.…”
Section: Discussioncontrasting
confidence: 82%
“…Body height showed only a slight influence on these groups, whereas sex had a strong correlation. A previous study 12 reported that the splenic flexure was located more cranially and more laterally in men than in women in an analysis of 100 CT images. Although the present series showed also that the individuals in the lateral group were predominantly men, the cranial group had a distinct location pattern of cranial, dorsal or medial, with nearly the same proportion in male and female patients.…”
Section: Discussionmentioning
confidence: 90%
“…We present a rare case of a retro‐pancreatic colonic splenic flexure 1,2 . The splenic flexure is the most superior and lateral section of the transverse colon related to the spleen 3 …”
Section: Figurementioning
confidence: 99%
“…1,2 The splenic flexure is the most superior and lateral section of the transverse colon related to the spleen. 3 A 69-year-old female underwent transanal endoscopic microscopic surgery to remove a 27 × 22 × 19 mm sessile rectal polyp. Histology confirmed a villous adenoma with high-grade dysplasia with a foci of invasion into the muscularis mucosae with one associated high-risk feature of lymphovascular invasion.…”
mentioning
confidence: 99%